Collaborative Border Management : A New Approach to an Old Problem - McLinden, Gerard (World Bank, Washington, DC, 2012)
Border clearance processes are among the most problematic links in the global supply chain and frequently undermine national competitiveness by increasing the cost of exports and reducing reliability of supply. As a result, securing meaningful reform of border management procedures has become an important issue for the development community. However, it remains an area where little effective guidance is available to reformers and development professionals. A recent publication released by the International Trade Department of the World Bank was developed in response to this need. The Border Management Modernization Handbook (World Bank 2011) outlines a new and more comprehensive reform and modernization agenda based on the concept of collaborative border management (CBM). The CBM concept shifts the focus beyond the traditional customs-specific trade facilitation agenda to a new and more comprehensive 'whole-of-government' approach to reform that relies less on institution-specific reform and more on a wider trade supply chain focused approach designed to tackle the major barriers traders face when navigating the frequently complex and opaque regulatory requirements that governments impose on international trade.